Peningkatan Literasi Digital Era New Normal: Studi Kasus Pembelajaran Daring Mahasiswa Akuntansi UPN Veteran Jawa Timur - Sholihatin, Endang; Widoretno, Astrini Aning; Haryono, Nanang; Dwi Aprilisanda, Invony; Korika Swasti, Ika; Kusumastuti, Erwin; Febrianita, Roziana (Akuntansi : Jurnal Akuntansi Integratif, 2021)
Abstract The rapid development of ICT and the digital world has changed many things. Education in the new normal era must innovate to integrate ICT. This study aims to determine the digital literacy competence of Accounting students FEB UPN Veteran East Java; and Formulating strategies to improve digital literacy competencies for Accounting students of FEB UPN Veterans East Java. In addition to digital infrastructure, it is necessary to design learning models such as curriculum that is integrated with digital literacy (Stein and Graham, 2014). European Commission Digital Competency Framework 2.1 (Carretero, Vuorikari & Punie, 2018), covers five aspects, namely information/data literacy; communication/collaboration; digital content creation; security; and problem solving. This research method uses mixed methods (survey/interview). Quantitative and qualitative data analysis. The results showed that from the five aspects of digital literacy competence, Accounting students of FEB UPN Veteran Jatim were categorized both in the aspects of Information/data literacy and Communication/collaboration. Next is the aspect of creating digital content; Security; and Troubleshooting, need improvement. Strategies to improve digital literacy competence are to direct students to: think critically; using digital media; manage online identity; managing digital distractions; digital experience practice; and get out of your comfort zone.